2008
DOI: 10.1152/ajplung.00247.2007
|View full text |Cite
|
Sign up to set email alerts
|

Altered carnitine homeostasis is associated with decreased mitochondrial function and altered nitric oxide signaling in lambs with pulmonary hypertension

Abstract: SM. Altered carnitine homeostasis is associated with decreased mitochondrial function and altered nitric oxide signaling in lambs with pulmonary hypertension. Am J Physiol Lung Cell Mol Physiol 294: L46-L56, 2008. First published November 16, 2007 doi:10.1152/ajplung.00247.2007.-Utilizing aortopulmonary vascular graft placement in the fetal lamb, we have developed a model (shunt) of pulmonary hypertension that mimics congenital heart disease with increased pulmonary blood flow. Our previous studies have ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
111
0
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
3
2
2

Relationship

4
3

Authors

Journals

citations
Cited by 82 publications
(127 citation statements)
references
References 75 publications
7
111
0
1
Order By: Relevance
“…Our recent studies have shown that increased CrAT nitration and decreased CrAT activity correlates with a disruption in carnitine homeostasis and NO signaling in Shunt lambs (42). To determine whether l-arginine supplementation could preserve carnitine homeostasis and mitochondrial function in Shunt lambs, we examined the effect of l-arginine supplementation on the levels of total protein nitration, CrAT activity, and CrAT nitration in control and Shunt lambs exposed to l-arginine (500 mg/kg/day) or vehicle for 3 weeks.…”
Section: L-arginine Supplementation Preserves Carnitine Homeostasis Amentioning
confidence: 93%
See 3 more Smart Citations
“…Our recent studies have shown that increased CrAT nitration and decreased CrAT activity correlates with a disruption in carnitine homeostasis and NO signaling in Shunt lambs (42). To determine whether l-arginine supplementation could preserve carnitine homeostasis and mitochondrial function in Shunt lambs, we examined the effect of l-arginine supplementation on the levels of total protein nitration, CrAT activity, and CrAT nitration in control and Shunt lambs exposed to l-arginine (500 mg/kg/day) or vehicle for 3 weeks.…”
Section: L-arginine Supplementation Preserves Carnitine Homeostasis Amentioning
confidence: 93%
“…Our previous studies demonstrated that increased levels of ADMA in Shunt lambs (47) correlated with a disruption in carnitine homeostasis and a loss of carnitine acetyl transferase (CrAT) activity (42). Carnitine homeostasis is of critical importance for maintaining oxidative phosphorylation (41).…”
Section: Adma Disrupts Carnitine Metabolism In Paecmentioning
confidence: 99%
See 2 more Smart Citations
“…Western Blot Analysis-Cells were prepared as previously described (21,22). Similarly, peripheral lung tissue from the control lambs and the lambs with pulmonary hypertension secondary to increased pulmonary blood flow (shunt) was prepared as described earlier (1).…”
Section: Methodsmentioning
confidence: 99%